PROBLEMATIKA IMPLEMENTASI HUKUM ISLAM DI INDONESIA Studi Kasus Pernikahan Pujiono dan Lutfiana Ulfa - Izzuddin, Ahmad (DE JURE, 2012)
The general principle of syari’ah states that legal majority comes with physical puberty. Hence in theory, capacity to conclude a marriage contract basically depends  upon proof of sexual maturity established under the normal rules of evidence rather than the attainment of a specific age. In examining the statutory measures on child marriage, it appears that the Compilation follows two main objectives:  restriction  and  indirect  prohibition.  Since  Muhammad  himself married Aisyah at an exceedingly tender age, so it is almost impossible for pious Muslims to condemn the practice. A punitive approach to child marriage would also seem unlikely to achieve a desirable result. The indirect means was therefore justified on the basis of the siyasah syar’iyah doctrine; instead of declaring the minor marriage void, the Compilation confined themselves to discouraging it by administrative expedients.